KUALITAS SEMEN CAIR BABI PERSILANGAN DENGAN PENGENCER BTS BERSUPLEMEN MADU PADA BERBAGAI KONSENTRASI (Effects of Different Honey Concentrations in BTS Diluent on Liquid Semen Quality of Crossbred Boars) - Yoachim Seplin Jas; Ni Luh Gde Sumardani; I Gede Mahardika (Universitas Nusa Cendana, 2026)
Honey is an organic substance that can be used as a semen extender supplement. This study aimed to evaluate the effect of honey supplementation in BTS (Beltsville Thawing Solution) diluent on the quality of liquid semen from crossbred boars. A completely randomized design (CRD) with four treatments and four replications was used. The treatments were: P0 = semen diluted with BTS without honey, P1 = BTS + 1% honey, P2 = BTS + 3% honey, and P3 = BTS + 5% honey. The observed variables were sperm motility, sperm viability, and semen pH after storage. Results showed that semen in P0 had the highest sperm motility and viability (62.5% and 80.5%, respectively), whereas all honey-supplemented treatments (P1, P2, P3) exhibited a significant decrease in semen quality (P < 0.05), with motility as low as 21.5% and viability as low as 48.5%. Semen pH did not differ significantly among treatments (P > 0.05). Biologically, these results indicate that honey supplementation in BTS diluent was unable to maintain semen quality. In conclusion, the highest quality liquid semen from crossbred boars was obtained using BTS diluent without honey.